2006
DOI: 10.1002/ejlt.200500250
|View full text |Cite
|
Sign up to set email alerts
|

Changes in nutraceutical lipid components of rice at different degrees of milling

Abstract: Changes in nutraceutical lipid components of rice at different degrees of millingThe concentrations of several nutraceutical lipid components [tocol (i.e. tocopherol 1 tocotrienol) phytosterol, g-oryzanol, octacosanol, and squalene] in milled rice and brown rice were determined. The lipid content decreased significantly (p ,0.05) as the degree of milling increased, as did the total tocol content. Significant differences (p ,0.05) were observed in the relative percentages of a-tocopherol, a-tocotrienol, and g-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 22 publications
7
36
1
3
Order By: Relevance
“…Of these, a-tocopherol was the most abundant in the oil, followed by a-tocotrienol and γ-tocotrienol. These results are consistent with the published reports of prior studies 19,20 .…”
Section: Tocols Concentrationssupporting
confidence: 94%
“…Of these, a-tocopherol was the most abundant in the oil, followed by a-tocotrienol and γ-tocotrienol. These results are consistent with the published reports of prior studies 19,20 .…”
Section: Tocols Concentrationssupporting
confidence: 94%
“…Currently, the consumer awareness of health food poducts is increasing and food scientists have been searching for interesting sources of healthul natural components. The results showed that rice bran extracts contain large amounts of nutraceticals with proven positive health effects (Ha et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…As most of these nutrients are contained in the rice bran [1], liposoluble nutrients are found in rice bran essential oil, which contains various kinds of physiologically active compounds, such as several phytosterols, γ-oryzanol, and vitamin E compounds, including tocopherols and tocotrienols. In addition to vitamin E action, tocopherols are known as antioxidants due to their chromanol ring [2,3], which affords an anti-inflammatory effect that reduces the risk of cardiovascular disease [4,5].…”
Section: Introductionmentioning
confidence: 99%